Kajian Pelaksanaan Metode Pembelajaran Suku Kata di Kelas 1 SDN 01 Anjongan - Rusmia, Rusmia; Yunika Afryaningsih; Salman Alfarisi (Jurnal Pendidikan Indonesia, 2025)
This research aims to determine the study of the implementation of the syllable learning method in class 1 of SDN 01 Anjongan carried out by class 1 teachers of SDN 01 Anjongan. A teacher needs the right method for the material to be conveyed. The learning method that must be chosen is to make it easier for students to begin reading. For example, when the syllable method was impllemented at SDN 01 Anjongan, the syllable metod was more effective than other learning methods. Therefore, the researcher focused his research which aims to fine out how the study of the implementation of the syllable learning method in class 1 SDN 01 Anjongan in the learning of beginning reading. This research uses a qualitative method, namely by describing the syllabic method implemented by the 1st grade teacher at SDN 01 Anjongan.the data collection techniques in form of interviews and observation form the two data colections are used as a whole according to needs. Matter this is so thst they can complement each other in corrcting the validity of the data collected. From the results of the research, it was found that the study of the implementation of the syllable larning method in reading learning at the beginning of grade 1 was very effective and had influence on the succes of the teaching and learning plrocess. In the school that was the object of research, the research admitted that this method had ofthen been used inlearning to read at the beginning because it was cosidered appropriate when used with lower grade students.